Inorganic chemistry - Housecroft, Catherine E., 1955- (Pearson Prentice Hall, 2008)
This new textbook brings a fresh and exciting approach to teaching modern inorganic chemistry. It includes many worked examples, taking the student through each calculation or exercise step-by-step.